Positive electrode material precursor with high capacity and cycle performance, preparation method of positive electrode material precursor, lithium ion battery, positive electrode material of lithium ion battery and lithium battery equipment
By adopting a block-like splicing arrangement of primary particles and feather-like unit structure in the precursor of the lithium-ion battery positive electrode material, the problem of reducing the cycle life of the medium-nickel ternary positive electrode material is solved, and the high capacity and circulation performance are achieved.
Patent Information
- Application Number
- CN202311099065.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-04
AI Technical Summary
While the existing medium nickel ternary cathode materials increase the energy density, the cycle life is significantly reduced, making it difficult to take into account both high capacity and cycling performance.
By adopting a block-like splicing arrangement of primary particles on the surface of the secondary particles of the positive electrode material precursor, and designing feather-like units and porous structures in the shell, the stability of the material and the lithium ion transport channel are improved.
It is achieved that the capacity performance of the medium nickel content positive electrode material is improved while retaining high cycling performance, making it comparable to the capacity effect of the high nickel content material.
Smart Images

Figure CN119551743A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a cathode material precursor and a preparation method thereof, a lithium-ion battery and its cathode material, and a lithium battery device having both high capacity and cycle performance. Background Art
[0002] Common cathode materials for lithium-ion batteries include lithium manganese oxide, lithium nickel oxide, lithium cobalt oxide, lithium iron phosphate and ternary materials. With the rapid development of electric vehicles and large-scale energy storage technology, people have put forward higher requirements on the capacity, power, cost, life and safety of lithium-ion batteries.
[0003] At present, ternary cathode materials have become mainstream products in the power battery industry. Studies have shown that increasing the nickel content in NCM materials can significantly increase their energy density, but increasing the nickel content in NCM will significantly reduce the cycle life of the material.
[0004] Therefore, how to develop a medium-nickel ternary positive electrode material that takes into account both capacity performance and cycle performance has become an urgent problem that needs to be solved in this field. Summary of the invention
[0005] The purpose of the present application is to provide a positive electrode material precursor and preparation method, a lithium-ion battery and its positive electrode material and lithium battery equipment that have both high capacity and cycle performance, so as to solve the above problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] In a positive electrode material precursor that takes both high capacity and cycle performance into consideration, primary particles located on the surface of secondary particles of the positive electrode material precursor are arranged in block-like splicing.
[0008] Preferably, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0009] A. The primary particles located on the surface of the secondary particles of the positive electrode material precursor are arranged in a block-like pattern;
[0010] B. The secondary particles of the positive electrode material precursor include a core layer, an intermediate layer and a shell layer, wherein the intermediate layer covers the core layer, and the shell layer covers the intermediate layer.
[0011] Preferably, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0012] C. The cross section of the shell layer includes a radial structure formed by a plurality of feather-like units arranged, wherein the feather-like unit includes a rachis portion and a vane portion, wherein the rachis portion is adjacent to the middle layer, and the vane portion is away from the middle layer;
[0013] Preferably, the average side length h1 of the feather-like unit is 3000-5000 nm, the average width b1 is 300-800 nm, and the average aspect ratio h1 / b1 is 4.0-11.0:1;
[0014] D. The secondary particles have pores on their surfaces, and the average pore size of the pores is 10-100 nm;
[0015] E. The surface of the secondary particles includes a plurality of primary particles satisfying the length a of 600-1800 nm and the width b of 200-900 nm; preferably, a / b is 1.5-5.1:1;
[0016] F. On the surface of the secondary particles, at least 50% of the primary particles satisfy a length a of 900-1600nm and a width b of 300-800nm, preferably, at least 50% of the primary particles satisfy a / b of 1.8-4.8:1;
[0017] G. The primary particles of the shell layer are in plate shape, the primary particles of the intermediate layer are in strip shape, and the primary particles of the core layer are in flake shape.
[0018] Preferably, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0019] (1) The specific surface area of the positive electrode material precursor is 2-7 m 2 / g;
[0020] (2) The tap density TD of the positive electrode material precursor is 2.0-2.4 g / cm 3 ;
[0021] (3) The peak intensity I of the positive electrode material precursor on the (101) crystal plane (101) The peak intensity I (001) Ratio I (101) / I (001) 1.0-1.7;
[0022] Preferably, I (101) / I (001) 1.1-1.2;
[0023] (4) The particle size D50 of the secondary particles of the positive electrode material precursor is 9-21 μm, preferably 12-16 μm;
[0024] (5) The particle size distribution span of the secondary particles of the positive electrode material precursor is 0.20-0.35;
[0025] Where, Span = (D90-D10) / D50;
[0026] (6) The sphericity of the secondary particles of the positive electrode material precursor is ≥ 0.95, preferably ≥ 0.98.
[0027] Preferably, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0028] (7) The diameter of the core layer is 1-3 μm, the thickness of the intermediate layer is 1-3 μm, and the thickness of the shell layer is 3-6 μm;
[0029] (8) The overall porosity of the secondary particles of the positive electrode material precursor is 5-12%, the porosity of the core layer is 20-40%, the porosity of the intermediate layer is 1-3%, and the porosity of the shell layer is 4-10%;
[0030] (9) The chemical formula of the positive electrode material precursor is Ni x Co y Mn (1-x-y-z) M z (OH)2, wherein 0.5≤x<0.8, 0≤y≤0.2, 0<1-xyz≤0.5, 0≤z≤0.2; M is selected from one or more of Mg, Al, Zr and Ca;
[0031] Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn (1-x-y-z) M z (OH)2, where 0.6≤x<0.8, y=0, 0.2<1-xyz≤0.4, 0≤z≤0.1;
[0032] (10) The particle crushing degree of the positive electrode material precursor is ΔDv3 / Dv3≤20%, preferably
[0033] ΔDv3 / Dv3≤10%;
[0034] Wherein, Dv3 refers to the particle size value when the cumulative volume distribution of the precursor secondary particle sample is 3%; ΔDv3 is the change value of the particle size before and after the cumulative volume distribution of the precursor secondary particle sample at 1T pressure is 3%;
[0035] The lower the ΔDv3 / Dv3 ratio, the smaller the particle size change under the action of external force, indicating that the secondary particle strength is higher.
[0036] The present application also provides a method for preparing a positive electrode material precursor having both high capacity and cycle performance, comprising:
[0037] The raw materials including the precipitant, the complexing agent and water are mixed to obtain a first base liquid, and then a metal salt solution, a complexing agent and a precipitant are added to the first base liquid to perform a coprecipitation reaction to obtain the positive electrode material precursor; the coprecipitation reaction temperature is 50°C-80°C.
[0038] Preferably, the preparation method satisfies one or more of the following conditions:
[0039] a. The specific steps of carrying out the coprecipitation reaction are: first, mixing raw materials including a precipitant, a complexing agent and water to obtain a first base liquid, then adding a metal salt solution, a complexing agent and a precipitant to the first base liquid to carry out a first reaction to obtain a crystal nucleus, then using the crystal nucleus, the precipitant and the complexing agent as a second base liquid, then adding a metal salt solution, a complexing agent and a precipitant to the second base liquid, and carrying out a second reaction to obtain the cathode material precursor;
[0040] b. The pH values of the first base liquid and the second base liquid are both 10.0-12.0;
[0041] c. During the first reaction process, the flow rate of the metal salt solution is 1-8% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-2.8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-0.24% / h of the available volume of the reaction vessel;
[0042] d. during the first reaction process, the pH value during the first reaction process is reduced and finally maintained at 9.5-11.5;
[0043] e. In the second reaction process, the flow rate of the metal salt solution is 1-12% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-4.2% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-12.03% / h of the available volume of the reaction vessel;
[0044] f. During the second reaction, the pH value during the second reaction is reduced and maintained unchanged, and then the pH value during the second reaction is reduced and finally maintained at 9.0-11.0;
[0045] g. After the coprecipitation reaction is completed, the further comprising: performing solid-liquid separation on the system after the coprecipitation reaction is completed, washing, drying, sieving and demagnetizing the solid;
[0046] h. During the coprecipitation reaction, the mother liquor produced in the coprecipitation reaction is continuously discharged.
[0047] The present application also provides a positive electrode material for a lithium-ion battery, wherein the raw material of the positive electrode material includes the positive electrode material precursor having both high capacity and cycle performance.
[0048] The present application also provides a lithium-ion battery, which includes the lithium-ion battery positive electrode material.
[0049] The present application also provides a lithium battery device, comprising the lithium-ion battery.
[0050] Compared with the prior art, the beneficial effects of this application include:
[0051] The positive electrode material precursor provided by the present application takes into account both high capacity and cycle performance, and the primary particles located on the surface of the secondary particles of the positive electrode material precursor are arranged in block splicing. Compared with needle-shaped or flaky primary particles, the primary particles on the surface of the product prepared by the present application are block-shaped, coarse particles, and not easy to break; and the primary particles on the surface are arranged in a splicing shape, so that the secondary particle structure is highly stable, the particle fragmentation is low, and the stress anisotropy is reduced, which can effectively inhibit the phase change of the crystal, and effectively improve the primary particle breakage that may be caused by the expansion and contraction of the material unit cell volume during the charge and discharge process, and the secondary particles are pulverized, thereby improving the cycle performance of the material. At the same time, under this morphology, there are 10-100nm pores between the primary particles on the surface, which provides a transmission channel for the deintercalation of lithium ions, which is beneficial to the use of capacity. The product prepared in the present application has a significant effect, while retaining high cycle performance, and the positive electrode material precursor with a medium nickel content (the molar ratio of nickel to the total metal is 0.5-0.8) achieves the same capacity effect as the positive electrode material precursor with a high nickel content (the molar ratio of nickel to the total metal is >0.9).
[0052] The present application provides a method for preparing a positive electrode material precursor that takes both high capacity and cycle performance into consideration, using an intermittent co-precipitation process, which is simple and stable.
[0053] The lithium-ion battery positive electrode material, lithium-ion battery and lithium battery equipment provided in this application have excellent electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0055] Figure 1 This is a SEM photo of the surface of the precursor secondary particles obtained in Example 1;
[0056] Figure 2 This is a SEM photo of the cross section of the precursor secondary particles obtained in Example 1;
[0057] Figure 3 This is a SEM photo of the surface of the precursor secondary particles obtained in Example 2;
[0058] Figure 4 This is a SEM photo of the cross section of the precursor secondary particles obtained in Example 2;
[0059] Figure 5 This is a SEM photo of the surface of the precursor secondary particles obtained in Example 3;
[0060] Figure 6 This is a SEM photo of the cross section of the precursor secondary particles obtained in Example 3;
[0061] Figure 7 This is a SEM photo of the surface of the precursor secondary particles obtained in Comparative Example 1;
[0062] Figure 8 This is a SEM photo of the cross section of the precursor secondary particles obtained in Comparative Example 1;
[0063] Fig. 9 This is a SEM photo of the surface of the precursor secondary particles obtained in Comparative Example 2;
[0064] Fig.10 This is a SEM photo of the cross section of the precursor secondary particles obtained in Comparative Example 2;
[0065] Fig.11 This is a SEM photo of the surface of the precursor secondary particles obtained in Comparative Example 3;
[0066] Fig.12 This is a SEM photograph of the cross-section of the precursor secondary particles obtained in Comparative Example 3. DETAILED DESCRIPTION
[0067] As used herein:
[0068] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0069] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0070] In these examples, parts and percentages are by mass unless otherwise indicated.
[0071] In a positive electrode material precursor with high cycle performance, primary particles located on the surface of secondary particles of the positive electrode material precursor are arranged in blocks.
[0072] In an optional embodiment, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0073] A. The primary particles on the surface of the secondary particles of the cathode material precursor are arranged in a block-like pattern;
[0074] It should be noted that the “quasi-square shape” referred to herein means that the primary particles on the surface of the secondary particles are relatively coarse and have a surface morphology similar to a square or rectangle; the spliced arrangement means that the primary particles on the surface of the secondary particles are arranged in a small puzzle-like pattern, the arrangement is relatively dense, and there are pores of 10-100 nm between the primary particles on the surface; and the primary particles on the surface are arranged in a small puzzle-like pattern. Figure 1 In this way, the surface of the secondary particle ball is relatively smooth, and the height difference between adjacent primary particles along the radial direction of the ball center is not large (that is, the surface of the secondary particle ball has a small degree of concavity and convexity).
[0075] B. The secondary particles of the positive electrode material precursor include a core layer, an intermediate layer and a shell layer. The intermediate layer covers the core layer, and the shell layer covers the intermediate layer.
[0076] In an optional embodiment, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0077] C. The cross section of the shell layer includes a radial structure formed by multiple feather-like units. The feather-like units include a rachis and a vane. The rachis is close to the middle layer, and the vane is far away from the middle layer.
[0078] It should be noted that the "feather-like unit" referred to here refers to the shell layer including a feather-like unit structure in the cross-sectional SEM photograph along the diameter direction of the precursor secondary particle with a magnification of 3000-10000 times. The feather-like unit has the same side length on both sides, the wider the feather part is farther away from the middle layer, and the narrower the feather shaft part is closer to the middle layer. There are no cracks visible to the naked eye inside the feather-like unit, and the structure is complete and not broken. The magnification of the SEM photo is based on the fact that there is only one complete or nearly complete secondary particle ball in the field of view of the SEM photo, the same below.
[0079] The cross-section of the shell in the three-layer structure includes a radial structure formed by the arrangement of multiple feather-like units, which is arranged compactly, further improving the integrity of the particles under external forces. The positive electrode material that inherits this structural feature has stronger bearing capacity and better compaction density, further improving the energy density of the battery cell.
[0080] In an optional embodiment, the average side length h1 of the feather-like unit is 3000-5000 nm, the average width b1 is 300-800 nm, and the average aspect ratio h1 / b1 is 4.0-11.0:1;
[0081] Optionally, the side length h1 of the feather-shaped unit may be 3000nm, 3500nm, 4000nm, 4500nm, 5000nm or any value between 3000-5000nm, the width b1 may be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm or any value between 300-800nm, and the aspect ratio h1 / b1 may be 4.0:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1 or any value between 4.0-11.0:1;
[0082] The method for measuring the data related to the feather-like unit is as follows: in the cross-sectional SEM photos along the diameter direction of the secondary particles of the precursor at a magnification of 3000-10000 times, the feather-like units that are not fully photographed at the edge of the photo and the non-feather-like units with irregular shapes and broken are screened out, and the feather-like units with complete structures and clear edges are selected. The longest side length and maximum width of each selected feather-like unit are measured respectively, and the average side length h1 and the average maximum width b1 are obtained after taking the average value. The average aspect ratio is calculated by calculating the aspect ratio of each selected feather-like unit, and then calculating the average aspect ratio of multiple feather-like units.
[0083] D. The secondary particles have pores on their surface, and the average pore size is 10-100 nm;
[0084] The method for measuring the average pore size of the surface pores is as follows: in the surface SEM photos of the precursor secondary particles with a magnification of 3000-10000 times, the surface pores that are not completely photographed, blurred, and distributed on the side of the field of view are screened out, and the surface pores that are complete, clear, and distributed on the front of the field of view are selected, and the maximum pore size of each selected surface pore is measured to calculate the average pore size of the surface pores;
[0085] Optionally, the average pore size of the secondary particle surface pores can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any value between 10-100 nm.
[0086] In addition, the shell of the secondary particles also has pores inside. From the cross-sectional SEM photos, there are narrow and long pores. The larger the ratio of the length to the width of the narrow and long pores (generally 10-80:1), the longer the inward pore path is, providing a good path for the insertion and extraction of lithium ions; but if the ratio is too large, the strength of the particles will decrease, affecting the cycle performance.
[0087] E. The surface of the secondary particles includes a plurality of primary particles satisfying a length of 600-1800 nm and a width of 200-900 nm; preferably, a / b is 1.5-5.1:1;
[0088] F. On the surface of the secondary particles, at least 50% of the primary particles satisfy the conditions that the length a is 900-1600nm and the width b is 300-800nm. Preferably, at least 50% of the primary particles satisfy the conditions that a / b is 1.8-4.8:1.
[0089] The method for measuring the data related to the primary particles on the surface of the shell layer is as follows: in the surface SEM photos of the precursor secondary particles with a magnification of 3000-10000 times, the primary particles that are not fully photographed at the edges of the photos, are blurred and blurred, and are on the side are screened out, and the complete, clear, and front primary particles are selected, and the longest straight line of each selected surface primary particle is measured as the length a, and the widest straight line perpendicular to the longest straight line is measured as the width b, to obtain the range of the length a and width b; the aspect ratio a / b of each surface primary particle is calculated to obtain the range of the aspect ratio a / b of the surface primary particles.
[0090] Optionally, the surface primary particle length a can be 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1700nm, 1800nm or any value between 600-1800nm, and the width b can be 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or any value between 200-900nm; preferably, a / b can be 1.5:1, 1.6:1, 1.7:1, 1.8:1. 1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5.0:1, 5.1:1 or any value between 1.5-5.1:1.
[0091] G. The primary particles of the shell layer are plate-shaped, the primary particles of the middle layer are strip-shaped, and the primary particles of the core layer are flake-shaped.
[0092] In an optional embodiment, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0093] (1) The specific surface area of the cathode material precursor is 2-7 m 2 / g;
[0094] Optionally, the BET surface area of the cathode material precursor may be 2 m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g or 2-7m 2 Any value between / g;
[0095] (2) The tap density TD of the cathode material precursor is 2.0-2.4 g / cm 3 ;
[0096] Optionally, the tap density TD of the cathode material precursor may be 2.0 g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3, 2.3g / cm 3 , 2.4g / cm 3 Or 2.0-2.4g / cm 3 Any value between
[0097] (3) Peak intensity I of cathode material precursor on (101) crystal plane (101) The peak intensity I (001) Ratio I (101) / I (001) 1.0-1.7;
[0098] Preferably, I (101) / I (001) 1.1-1.2;
[0099] Optionally, the peak intensity I of the cathode material precursor on the (101) crystal plane is (101) The peak intensity I (001) Ratio I (101) / I (001) It can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or any value between 1.0 and 1.7;
[0100] (4) The particle size D50 of the secondary particles of the positive electrode material precursor is 9-21 μm, preferably 12-16 μm;
[0101] Optionally, the particle size D50 of the secondary particles of the positive electrode material precursor may be 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm or any value between 9 and 21 μm;
[0102] (5) The particle size distribution span of the secondary particles of the cathode material precursor is 0.20-0.35;
[0103] Optionally, the particle size distribution Span of the secondary particles of the positive electrode material precursor may be 0.20, 0.25, 0.30, 0.35 or any value between 0.20 and 0.35;
[0104] (6) The sphericity of the secondary particles of the positive electrode material precursor is ≥ 0.95, preferably ≥ 0.98;
[0105] Optionally, the sphericity of the secondary particles of the positive electrode material precursor may be 0.95, 0.96, 0.97, 0.98, 0.99, 0.995, 0.998, 0.999 or any value between 0.95 and 1.
[0106] In an optional embodiment, the cathode material precursor having both high capacity and cycle performance satisfies one or more of the following conditions:
[0107] (7) The diameter of the core layer is 1-3 μm, the thickness of the middle layer is 1-3 μm, and the thickness of the shell layer is 3-6 μm;
[0108] Optionally, the diameter of the core layer may be 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm or any value between 1-3 μm, the thickness of the intermediate layer may be 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm or any value between 1-3 μm, and the thickness of the shell layer may be 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm or any value between 3-6 μm;
[0109] (8) The overall porosity of the secondary particles of the positive electrode material precursor is 5-12%, the porosity of the core layer is 20-40%, the porosity of the middle layer is 1-3%, and the porosity of the shell layer is 4-10%;
[0110] The presence of abundant pores on the surface, narrow and long pores on the cross section and appropriate porosity help the lithium salt to enter the interior of the precursor for sufficient reaction, provide a good channel for the transmission of lithium ions during the charge and discharge process, and facilitate the utilization of capacity.
[0111] Optionally, the overall porosity of the secondary particles of the positive electrode material precursor may be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or any value between 5-12%, the porosity of the core layer may be 20%, 25%, 30%, 35%, 40% or any value between 20-40%, the porosity of the intermediate layer may be 1%, 2%, 3% or any value between 1-3%, and the porosity of the shell layer may be 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 4-10%;
[0112] (9) The chemical formula of the cathode material precursor is Ni x Co y Mn (1-x-y-z) M z (OH)2, wherein 0.5≤x<0.8, 0≤y≤0.2, 0<1-xyz≤0.5, 0≤z≤0.2; M is selected from one or more of Mg, Al, Zr and Ca;
[0113] In an optional embodiment, the chemical formula of the positive electrode material precursor is Ni x Co y Mn (1-x-y-z) M z(OH)2, wherein 0.6≤x<0.8, y=0, 0.2<1-xyz≤0.4, 0≤z≤0.1.
[0114] Optionally, x can be 0.5, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79 or y can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2 or any value between 0 and 0.2; 1-xyz can be 0.1, 0.11, 0.12, 0.13, 0.14、0.15、0.16、0.17、0.18、0.19、0.2、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29、0.3、0.31、0.32、0.33、0.34、0.35、0.36、0.37、0.38、0.39、0.4、0.41、0.42、0.43、0.44、0.45、0 .46, 0.47, 0.48, 0.49, 0.5 or any value greater than 0 and less than or equal to 0.5; z can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2 or any value between 0 and 0.2.
[0115] Preferably, when y=0, 0.6≤x<0.8, 0.2<1-xyz≤0.4, 0≤z≤0.1, a cobalt-free and medium-nickel series product is obtained. Under the three-layer structure and the feather-like shell structure, the primary particles have good crystallinity and can well balance the capacity and cycle performance.
[0116] (10) The particle crushing degree of the positive electrode material precursor is ΔDv3 / Dv3≤20%, preferably ΔDv3 / Dv3≤10%;
[0117] Particle breakage test method: Before the test, test the particle size Dv3 of the sample and record it. Weigh about 2g of the sample and put it into the mold of a microcomputer electronic pressure testing machine (mold shape: a cylinder with a diameter of 13mm) for testing. Set the applied pressure to 1T. When the pressure rises to the set value 1T, take out the material and test the particle size Dv3' and record it.
[0118] Wherein, Dv3 refers to the particle size value of the precursor secondary particle sample before the particle crushing degree test when the cumulative volume distribution is 3%; Dv3' refers to the particle size value of the precursor secondary particle sample after the particle crushing degree test when the cumulative volume distribution is 3%; ΔDv3 is the change value of the particle size before and after the cumulative volume distribution of the precursor secondary particle sample at 1T pressure is 3%, and the calculation formula is: ΔDv3 = Dv3-Dv3';
[0119] The lower the ΔDv3 / Dv3 ratio, the smaller the particle size change under the action of external force, indicating that the secondary particle strength is higher.
[0120] The present application also provides a method for preparing a positive electrode material precursor having both high capacity and cycle performance, comprising:
[0121] The raw materials including the precipitant, the complexing agent and water are mixed to obtain a first base liquid, and then a metal salt solution, a complexing agent and a precipitant are added to the first base liquid to perform a coprecipitation reaction to obtain a positive electrode material precursor; the coprecipitation reaction temperature is 50°C-80°C.
[0122] Optionally, the coprecipitation reaction temperature can be 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C or any value between 50°C and 80°C.
[0123] High temperature reaction helps to make the primary particles coarser, with better crystallinity and stronger bearing capacity, thus improving the battery cycle performance.
[0124] In an optional embodiment, the preparation method satisfies one or more of the following conditions:
[0125] a. The specific steps of the coprecipitation reaction are: first, mixing raw materials including a precipitant, a complexing agent and water to obtain a first base liquid, then adding a metal salt solution, a complexing agent and a precipitant to the first base liquid to perform a first reaction to obtain a crystal nucleus, then using the crystal nucleus, the precipitant and the complexing agent as a second base liquid, and then adding a metal salt solution, a complexing agent and a precipitant to the second base liquid to perform a second reaction to obtain a cathode material precursor;
[0126] b. The pH values of the first base solution and the second base solution are both 10.0-12.0;
[0127] Optionally, the pH value of the first base liquid and the second base liquid can independently be 10.0, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0 or any value between 10.0 and 12.0;
[0128] c. During the first reaction, the flow rate of the metal salt solution is 1-8% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-2.8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-0.24% / h of the available volume of the reaction vessel;
[0129] Optionally, the flow rate of the metal salt solution can be 1% / h, 2% / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h or any value between 1-8% / h of the available volume of the reaction vessel, the flow rate of the precipitant can be 0.35% / h, 0.50% / h, 1.0% / h, 1.5% / h, 2.0% / h, 2.5% / h, 2.8% / h or any value between 0.35-2.8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent can be 0.03% / h, 0.05% / h, 0.10% / h, 0.15% / h, 0.20% / h, 0.24% / h or any value between 0.03-0.24% / h of the available volume of the reaction vessel;
[0130] d. During the first reaction, the pH value during the first reaction is reduced and finally maintained at 9.5-11.5;
[0131] Optionally, the pH may be ultimately maintained at 9.5, 10.0, 10.5, 11.0, 11.5, or any value between 9.5 and 11.5;
[0132] e. During the second reaction, the flow rate of the metal salt solution is 1-12% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-4.2% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-12.03% / h of the available volume of the reaction vessel;
[0133] Optionally, in the second reaction process, the flow rate of the metal salt solution can be 1% / h, 2% / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h, 9% / h, 10% / h, 11% / h, 12% / h or any value between 1% and 12% / h of the available volume of the reaction container, and the flow rate of the precipitant can be 0.35% / h, 0.50% / h, 1.0% / h, 1.5% / h, 2.0% / h, 2.5% / h, 3.0% / h, 3.5% / h, 4.0% / h, 5.0% / h, 6.0% / h, 7.0% / h, 8.0% / h, 9.0% / h, 10.0% / h, 11.0% / h, 12 ... 5% / h, 4.0% / h, 4.2% / h or any value between 0.35-4.2% / h, the flow rate of the complexing agent is 0.03% / h, 0.05% / h, 0.10% / h, 0.50% / h, 1% / h, 2% / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h, 9% / h, 10% / h, 11% / h, 12% / h, 12.03% / h or any value between 0.03-12.03% / h of the available volume of the reaction vessel;
[0134] f. During the second reaction, the pH value during the second reaction is lowered and maintained unchanged, and then the pH value during the second reaction is lowered and finally maintained at 9.0-11.0;
[0135] Here, "maintaining unchanged" means that after the pH is adjusted, the pH in the system is kept unchanged within a set time; and the reaction is carried out in this state.
[0136] Optionally, the pH may be ultimately maintained at 9.0, 9.5, 10.0, 10.5, 11.0 or any value between 9.0 and 11.0;
[0137] g. After the coprecipitation reaction is completed, the coprecipitation reaction system is further comprised of: solid-liquid separation, washing, drying, sieving, and demagnetizing the solids;
[0138] h. During the coprecipitation reaction, the mother liquor produced in the coprecipitation reaction is continuously discharged.
[0139] The present application also provides a positive electrode material for a lithium-ion battery, wherein the raw materials of the positive electrode material include a positive electrode material precursor that has both high capacity and cycle performance.
[0140] The present application also provides a lithium-ion battery, which includes a lithium-ion battery positive electrode material.
[0141] The present application also provides a lithium battery device, including a lithium-ion battery.
[0142] It can be understood that the lithium battery equipment referred to in this application can be a device that directly uses the lithium-ion battery provided by this application for power supply, such as an electric car, an electric bicycle, etc., or it can be a device that uses the lithium-ion battery provided by this application for energy storage, such as an energy storage system.
[0143] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0144] Example 1
[0145] This embodiment provides a positive electrode material precursor having both high capacity and cycle performance, and the preparation method thereof comprises the following steps:
[0146] Step 1: Calculate and weigh nickel sulfate crystals and manganese sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to a nickel-manganese metal molar ratio of 75:25; prepare a sodium hydroxide solution with a concentration of 32%, and prepare an ammonia solution with a concentration of 21%;
[0147] Step 2, adding pure water, sodium hydroxide solution and ammonia water into the reaction kettle, and stirring evenly at 220 r / min, and keeping the temperature at 55° C. to obtain a first bottom liquid with a pH value of 11.2 and an ammonia concentration of 3.5 g / L;
[0148] Step 3, the above metal salt solution, sodium hydroxide solution, and ammonia water are respectively introduced into the reactor to which the first bottom liquid has been added at a flow rate of 1% / h, 0.35% / h, and 0.03% / h of the available reactor volume to carry out the first reaction, and the temperature is kept at 55°C. After the reaction starts, the pH value is reduced by 0.1 units within 4 hours by adjusting the flow rate of sodium hydroxide and maintained for 4 hours, and then the pH value is further reduced, and the final pH value is maintained at 10.4-10.6. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-manganese precipitate with a medium particle size D50 of 5.3μm is obtained, the reaction precipitate is dehydrated and dried; it is used as the crystal nucleus for the next reaction to continue the growth reaction;
[0149] Step 4: Put the crystal nucleus obtained in step 3 into the reactor, add water, sodium hydroxide solution and ammonia water to obtain a second bottom solution with a pH value of 10.6 and an ammonia concentration of 6.0 g / L. The metal salt solution, sodium hydroxide solution and ammonia water are continuously introduced into the reactor at a flow rate of 1% / h, 0.35% / h and 0.03% / h of the available reactor volume, respectively, and the temperature is kept at 70°C. After the reaction precipitation starts, the pH is reduced by 0.2 within 6 hours by adjusting the sodium hydroxide flow rate, and the pH is maintained unchanged for 4 hours, after which the pH continues to decrease, and the final pH is maintained at 10.0-10.2. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-manganese precipitate with a D50 of 14.3 μm is obtained.
[0150] Step 5: Wash, centrifuge, dry, and sieve the nickel-manganese precipitate to remove magnetism, and obtain the positive electrode material precursor Ni 0.75 Mn 0.25 (OH)2.
[0151] Under the scanning electron microscope SEM: The SEM photo of the surface of the precursor secondary particles is as follows: Figure 1 As shown in Figure 2, the secondary particles have a small surface roughness and good sphericity; the SEM photo of the cross section is shown in Figure 2. Figure 2 As shown, the cross-section presents a three-layer structure, the core layer is loose and presents a reticular structure, the middle layer is loose and presents a radially staggered structure; the shell layer includes a radial structure formed by a plurality of feather-like units, the feather-like unit includes a rachis part and a vane part, the rachis part is close to the middle layer, the vane part is far away from the middle layer, and the closer to the surface of the secondary particle, the wider it is.
[0152] Example 2
[0153] Compared with Example 1, the difference between this embodiment and Example 1 is that step 1: calculate and weigh nickel sulfate crystals, manganese sulfate crystals, and aluminum sulfate crystals, and configure them into a metal salt solution with a total metal molar amount of 2 mol / L according to a metal molar ratio of nickel, manganese, and aluminum of 75:24:1; during the reaction, the mother liquor is discharged through a concentration device, and the discharge rate is consistent with the total feed amount; until a positive electrode material precursor Ni with a D50 of 12.7 μm is obtained 0.75 Mn 0.24 Al 0.01 (OH)2.
[0154] The SEM images of the surface of the obtained precursor secondary particles are as follows: Figure 3 As shown in FIG. 1 , the secondary particles have a smaller surface roughness and a better sphericity, and the primary particles on the surface are more densely arranged compared to Example 1; the SEM photo of the cross section is shown in FIG. Figure 4As shown, the cross-section presents a three-layer structure, the core layer is loose and presents a mesh structure, the middle layer is loose and presents a radially staggered structure; the shell layer includes a radial structure formed by a plurality of feather-like units, the feather-like unit includes a rachis portion and a vane portion, the rachis portion is close to the middle layer, the vane portion is far away from the middle layer, and the closer to the secondary particle surface, the wider it is, and relative to Example 1, the cross-section photograph has better glossiness, which is presumably due to the change caused by aluminum doping.
[0155] Example 3
[0156] Step 1: Calculate and weigh nickel sulfate crystals, manganese sulfate crystals, and aluminum sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to a metal molar ratio of nickel, manganese, and aluminum of 65:5:30; prepare a sodium hydroxide solution with a concentration of 32%, and prepare an ammonia solution with a concentration of 21%;
[0157] Step 2, add pure water, sodium hydroxide solution and ammonia water into the reactor, and stir evenly at 220r / min, keep the temperature at 55°C, and obtain a first bottom liquid with a pH value of 11.7 and an ammonia concentration of 3.5g / L;
[0158] Step 3, the above metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor to which the first bottom liquid has been added at flow rates of 1.5% / h, 0.75% / h, and 0.045% / h of the available reactor volume, respectively, to carry out the first reaction, and the temperature is kept at 55°C. After the reaction precipitation begins, the pH is allowed to drop by 0.2 within 8 hours by adjusting the flow rate of sodium hydroxide, and then the pH continues to drop, and the final pH value is maintained at 10.4-10.6. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-cobalt-manganese precipitate with a medium particle size D50 of 5.1μm is obtained, the reaction precipitate is dehydrated and dried; it is used as the crystal nucleus for the next reaction to continue the growth reaction;
[0159] Step 4, put the crystal nuclei obtained in step 3 into the reactor, add water, sodium hydroxide solution and ammonia water to obtain a second bottom liquid with a pH value of 10.0 and an ammonia concentration of 3.25g / L. Continue to simultaneously introduce the metal salt solution, sodium hydroxide solution and ammonia water into the reactor at a flow rate of 4.5% / h, 1.58% / h and 0.14% / h of the available reactor volume, respectively, at a constant temperature of 80°C. After the reaction precipitation starts, adjust the sodium hydroxide flow rate to allow the pH to drop by 0.4 within 3 hours, and maintain the pH at 9.5-9.7. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-manganese precipitate with a D50 of 12.4μm is obtained;
[0160] Step 5: Wash, centrifuge, dry, and sieve the precipitate to remove magnetism, and obtain the positive electrode material precursor Ni 0.65 Co 0.05 Mn0.30 (OH)2.
[0161] The SEM images of the surface of the obtained precursor secondary particles are as follows: Figure 5 As shown in FIG. 1 , the secondary particles have a smaller surface concavity and convexity and a better sphericity. Compared with Example 1, the primary particles on the surface are more sparsely arranged and the aspect ratio a / b of the primary particles is larger. The SEM photo of the cross section is shown in FIG. Figure 6 As shown, the cross-section presents a three-layer structure, the core layer is loose and presents a reticular structure, the middle layer is loose and presents a radially staggered structure; the shell layer includes a radial structure formed by a plurality of feather-like units, the feather-like unit includes a rachis part and a vane part, the rachis part is close to the middle layer, the vane part is far away from the middle layer, and the closer to the surface of the secondary particle, the wider it is.
[0162] Comparative Example 1
[0163] This comparative example provides a lithium ion battery positive electrode material precursor, and the preparation method thereof comprises the following steps:
[0164] Step 1: Calculate and weigh nickel sulfate crystals, cobalt sulfate crystals, and manganese sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to the metal molar ratio of nickel to manganese of 90:6:4; prepare a sodium hydroxide solution with a concentration of 32%, and prepare an ammonia solution with a concentration of 21%;
[0165] Step 2: Add pure water, sodium hydroxide solution and ammonia water into the reactor, stir evenly at 388 r / min, keep the temperature at 45°C, and obtain a first bottom solution with a pH value of 12.0 and an ammonia concentration of 8.0 g / L;
[0166] Step 3, the metal salt solution, sodium hydroxide solution and ammonia water are respectively introduced into the reactor to which the bottom liquid has been added at a flow rate of 4.2% / h, 1.55% / h and 0.13% / h of the available reactor volume to carry out a coprecipitation reaction, and the temperature is kept at 45°C. After the reaction starts, the pH is reduced by 0.1 unit within 3 hours by adjusting the flow rate of sodium hydroxide, and then the pH is reduced within 9 hours and maintained at 10.2-10.4. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-cobalt-manganese precipitate with a medium particle size D50 of 3.5 μm is obtained.
[0167] The precipitate is washed, centrifuged, dried, sieved and demagnetized to obtain the positive electrode material precursor Ni 0.90 Co 0.06 Mn 0.04 (OH)2.
[0168] Under a scanning electron microscope: the surface of the precursor secondary particles has a larger surface roughness than the primary particles (e.g. Figure 7 ), but the interior is a dense two-layer structure with fewer pores and no feather-like unit features (such as Figure 8 shown).
[0169] Comparative Example 2
[0170] This comparative example provides a lithium ion battery positive electrode material precursor, and the preparation method thereof comprises the following steps:
[0171] Step 1: Calculate and weigh nickel sulfate crystals, cobalt sulfate crystals, and manganese sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to the metal molar ratio of nickel, cobalt, and manganese at a ratio of 83:7:10; prepare a sodium hydroxide solution with a concentration of 32% and an ammonia solution with a concentration of 21%;
[0172] Step 2: Add pure water, sodium hydroxide solution and ammonia water into the reactor, stir evenly at 220 r / min, keep the temperature at 60° C., and obtain a first bottom solution with a pH value of 11.6 and an ammonia concentration of 5.0 g / L;
[0173] Step 3, the metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor to which the qualified bottom liquid has been added at a flow rate of 2.0% / h, 0.74% / h, and 0.06% / h of the available reactor volume, respectively, and the temperature is kept at 60°C. After the reaction precipitation begins, the pH is lowered within 6 hours by adjusting the flow rate of sodium hydroxide and maintained at 10.9-11.1. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-cobalt-manganese precipitate with a medium particle size D50 of 3.0μm is obtained, the reaction precipitate is dehydrated and dried; it is used as the crystal nucleus for the next reaction to continue the growth reaction;
[0174] Step 4: Put the nickel-manganese precipitate obtained in step 3 into a reactor, add water, sodium hydroxide solution and ammonia water to obtain a second bottom solution with a pH value of 10.8 and an ammonia concentration of 4.5 g / L. The metal salt solution, sodium hydroxide solution and ammonia water are continuously introduced into the reactor at a flow rate of 2% / h, 0.74% / h and 0.06% / h of the available reactor volume, respectively, at a constant temperature of 60°C. After the reaction precipitation starts, the pH is adjusted by adjusting the sodium hydroxide flow rate to increase by 0.1 within 7 hours, and the pH is maintained unchanged for 9 hours, and then the pH is increased within 5 hours and maintained at 11.3-11.5. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-cobalt-manganese precipitate with a D50 of 10.2 μm is obtained.
[0175] Step 5: Wash, centrifuge, dry, and sieve the reaction precipitate to remove magnetism, and obtain the positive electrode material precursor Ni 0.83 Co 0.07 Mn 0.10 (OH)2.
[0176] Under a scanning electron microscope: the surface is velvety, with large concavity and convexity, poor consistency of primary particle size, and irregular arrangement (such as Fig. 9 As shown), the internal section is a three-layer structure, the shell has a feather-like unit similar to that of Example 1, which is composed of multiple small units. There are multiple cracks inside the feather-like unit, which are densely arranged (as shown in FIG. Fig.10 shown).
[0177] Comparative Example 3
[0178] Compared with Example 1, the difference between this comparative example and Example 1 is that in step 4: after the reaction precipitation starts, the pH is reduced by 0.1 within 7 hours by adjusting the flow rate of sodium hydroxide, and the pH is maintained unchanged for 4 hours, and then the pH is reduced within 5 hours and finally maintained at 9.6-9.8. During the reaction, the mother liquor is discharged through the concentration device, and the discharge rate is consistent with the total feed amount; until a nickel-manganese precipitate with a D50 of 14.1 μm is obtained.
[0179] The reaction precipitate is washed, centrifuged, dried, sieved and demagnetized to obtain the positive electrode material precursor Ni 0.75 Mn 0.25 (OH)2.
[0180] Under a scanning electron microscope: the surface is spindle-shaped and interwoven, the primary particles are spindle-shaped, the surface is porous, and there are many surface pores (such as Fig.11 The internal section shows a three-layer structure, the core layer is loose and reticular, the middle layer is loose and radially staggered; the shell layer is loose and radially arranged, and the primary particles of the shell layer are finer (as shown in Fig.12 shown).
[0181] The precursors obtained in the examples and comparative examples were subjected to physical and chemical tests, and the results are shown in Tables 1-5 below:
[0182] Table 1 Precursor surface morphology and data
[0183]
[0184] Note: According to the measurement method of the primary particles related data on the shell surface, select 50% of the primary particles with larger size from the selected primary particles on the shell surface, measure the length a and width b and calculate a / b.
[0185] Table 2 Shell morphology and data in the precursor section
[0186]
[0187] Table 3 Precursor intermediate layer and shell layer data
[0188]
[0189] Table 4 Precursor physicochemical data 1
[0190]
[0191] Table 5 Precursor physicochemical data 2
[0192]
[0193] Cathode material preparation:
[0194] 2000g of the precursors prepared in Examples 1-3 and Comparative Examples 1-3 and LiOH were respectively mixed uniformly in a high-speed mixer at a molar ratio of 1:1.05, and sintered in a box furnace under air atmosphere at a sintering temperature of 900-950°C for 10-12h. After cooling to room temperature, the positive electrode material was obtained.
[0195] Battery preparation:
[0196] The electrochemical performance test was carried out using a button-type semi-electric battery: the above-mentioned positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry in a ratio of 92.5:5:2.5, and coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into a button battery in a vacuum glove box. The Blue Electric test system was used to test the 0.1C charge and discharge performance at room temperature within the range of 3.0-4.3V, and the 50-week capacity retention rate was tested at 0.5C at 45°C. The electrochemical performance test was carried out using a Blue Electric button test cabinet. The test electrochemical data are shown in Table 6:
[0197] Table 6 Electrochemical data
[0198]
[0199] By the attached Figure 1-12 From Table 1-6 above, we can see that:
[0200] The positive electrode material precursors prepared in Examples 1, 2, and 3 have primary particles on the surface of the secondary particles of the positive electrode material precursors arranged in block-like splicing, with a highly stable structure and low particle fragmentation, which can effectively improve the particle pulverization during the charge and discharge process, thereby improving the cycle performance of the material. At the same time, under this morphology, there are 10-100nm pores between the primary particles on the surface, which provides a transmission channel for the deintercalation of lithium ions, which is beneficial to the performance of capacity. The internal shell is relatively thick, the radial structure of the feather-like unit has a high degree of regularity, a stable structure, and a certain number of narrow and long holes inside, taking into account both capacity performance and cycle performance.
[0201] Compared with Example 2, the pore spacing between the primary particles on the surface of Example 1 is wider, showing better capacity performance, and the 0.1C discharge capacity is increased by 6.7 mAh / g. The aluminum-doped product obtained in Example 2 has a relatively small pore spacing between the primary particles on the shell surface, and the particle crushing degree is reduced by 3.1% compared with Example 1, showing better cycle performance, and the capacity retention rate after 50 cycles is increased by 1.1%.
[0202] The product obtained in Example 3 has a larger surface average pore size than that in Example 1, and the particle breakage degree is increased by 2.8% compared with that in Example 1, showing slightly poor cycle performance, and the capacity retention rate after 50 cycles is reduced by 0.2%. Compared with Example 2, the particle breakage degree is increased by 5.9% compared with that in Example 2, showing slightly poor cycle performance, and the capacity retention rate after 50 cycles is reduced by 1.3%. However, at the same time, the pores with larger surface pore size are also conducive to the deintercalation of lithium ions, showing better capacity performance than that in Example 2, and the 0.1C discharge capacity is increased by 4.8 mAh / g.
[0203] Compared with Examples 1-3, the product obtained in Comparative Example 1 is small particles with a staggered arrangement of long strips on the surface, slightly poor regularity of the primary particles in the shell layer, no feather-like structure, a dense interior, and fewer pores. The positive electrode material inheriting this structure is not conducive to the deintercalation of lithium ions, so it exhibits poor capacity performance and a reduced 0.1C discharge capacity; however, due to the dense internal structure and good bearing pressure, it exhibits excellent cycle performance, but is limited by the irregularity of the primary particles that constitute the shell layer, and the final capacity retention rate after 50 cycles is reduced.
[0204] Compared with Examples 1-3, the product obtained in Comparative Example 2 is large particles, with a pompom-like surface and a large degree of concavity and convexity. The internal structure is a dense arrangement of spliced feather-like units with a low porosity. The positive electrode material inheriting this structure is not conducive to the deintercalation of lithium ions, so it exhibits poor capacity and a reduced 0.1C discharge capacity. The primary particles of the shell layer are finer, shorter and irregular, but densely arranged. The positive electrode material inheriting this structure has good bearing pressure, a slightly larger particle breakage degree, and overall good cycle data. The final capacity retention rate for 50 cycles is between that of Example 1 and Example 2.
[0205] Compared with Examples 1-3, the product obtained in Comparative Example 3 is a large-particle product, whose primary particles are slender, spindle-shaped, have many narrow pores, and have a high surface porosity, which provides a favorable channel for the deintercalation of lithium ions, showing an increase in capacity; however, the strength of the structural particles is poor. Under the same pressure, the particle breakage degree is the worst, which is much lower than that of Examples 1 and 2, and the cycle performance is the worst, and the capacity retention rate after 50 cycles is reduced.
[0206] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0207] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A positive electrode material precursor having both high capacity and cycle performance, characterized in that: In the positive electrode material precursor, the primary particles located on the surface of the secondary particles of the positive electrode material precursor are arranged in blocks.
2. The positive electrode material precursor having both high capacity and cycle performance according to claim 1, characterized in that: One or more of the following conditions are met: A. The primary particles located on the surface of the secondary particles of the positive electrode material precursor are arranged in a block-like pattern; B. The secondary particles of the positive electrode material precursor include a core layer, an intermediate layer and a shell layer, wherein the intermediate layer covers the core layer, and the shell layer covers the intermediate layer.
3. The cathode material precursor having both high capacity and cycle performance according to claim 2, characterized in that: One or more of the following conditions are met: C. The cross section of the shell layer includes a radial structure formed by a plurality of feather-like units arranged, wherein the feather-like unit includes a rachis portion and a vane portion, wherein the rachis portion is adjacent to the middle layer, and the vane portion is away from the middle layer; Preferably, the average side length h1 of the feather-like unit is 3000-5000 nm, the average width b1 is 300-800 nm, and the average aspect ratio h1 / b1 is 4.0-11.0:1; D. The secondary particles have pores on their surfaces, and the average pore diameter of the pores is 10-100 nm; E. The surface of the secondary particles includes a plurality of primary particles satisfying the length a of 600-1800 nm and the width b of 200-900 nm; preferably, a / b is 1.5-5.1:1; F. On the surface of the secondary particles, at least 50% of the primary particles satisfy the conditions that the length a is 900-1600nm and the width b is 300-800nm. Preferably, at least 50% of the primary particles satisfy the conditions that a / b is 1.8-4.8:
1.
4. The cathode material precursor having both high capacity and cycle performance according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The specific surface area of the positive electrode material precursor is 2-7 m 2 / g; (2) The tap density TD of the positive electrode material precursor is 2.0-2.4 g / cm 3 ; (3) The peak intensity I of the positive electrode material precursor on the (101) crystal plane (101) The peak intensity I (001) Ratio I (101) / I (001) 1.0-1.7; Preferably, I (101) / I (001) 1.1-1.2; (4) The particle size D50 of the secondary particles of the positive electrode material precursor is 9-21 μm, preferably 12-16 μm; (5) The particle size distribution span of the secondary particles of the positive electrode material precursor is 0.20-0.35; (6) The sphericity of the secondary particles of the positive electrode material precursor is ≥ 0.95, preferably ≥ 0.
98.
5. The positive electrode material precursor having both high capacity and cycle performance according to claim 2 or 3, characterized in that: One or more of the following conditions are met: (7) The diameter of the core layer is 1-3 μm, the thickness of the intermediate layer is 1-3 μm, and the thickness of the shell layer is 3-6 μm; (8) The overall porosity of the secondary particles of the positive electrode material precursor is 5-12%, the porosity of the core layer is 20-40%, the porosity of the intermediate layer is 1-3%, and the porosity of the shell layer is 4-10%; (9) The chemical formula of the positive electrode material precursor is Ni x Co y Mn (1-x-y-z) M z (OH)2, wherein 0.5≤x<0.8, 0≤y≤0.2, 0<1-xyz≤0.5, 0≤z≤0.2; M is selected from one or more of Mg, Al, Zr and Ca; Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn (1-x-y-z) M z (OH)2, wherein 0.6≤x<0.8, y=0, 0.2<1-xyz≤0.4, 0≤z≤0.
1.
6. A method for preparing a positive electrode material precursor having both high capacity and cycle performance as claimed in any one of claims 1 to 5, characterized in that: include: The raw materials including the precipitant, the complexing agent and water are mixed to obtain a first base liquid, and then a metal salt solution, a complexing agent and a precipitant are added to the first base liquid to perform a coprecipitation reaction to obtain the positive electrode material precursor; the coprecipitation reaction temperature is 50°C-80°C.
7. The preparation method according to claim 6, characterized in that: One or more of the following conditions are met: a. The specific steps of carrying out the coprecipitation reaction are: first, mixing raw materials including a precipitant, a complexing agent and water to obtain a first base liquid, then adding a metal salt solution, a complexing agent and a precipitant to the first base liquid to carry out a first reaction to obtain a crystal nucleus, then using the crystal nucleus, the precipitant and the complexing agent as a second base liquid, then adding a metal salt solution, a complexing agent and a precipitant to the second base liquid, and carrying out a second reaction to obtain the cathode material precursor; b. The pH values of the first base liquid and the second base liquid are both 10.0-12.0; c. During the first reaction process, the flow rate of the metal salt solution is 1-8% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-2.8% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-0.24% / h of the available volume of the reaction vessel; d. during the first reaction process, the pH value during the first reaction process is reduced and finally maintained at 9.5-11.5; e. In the second reaction process, the flow rate of the metal salt solution is 1-12% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-4.2% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-12.03% / h of the available volume of the reaction vessel; f. During the second reaction, the pH value during the second reaction is lowered and maintained unchanged, and then the pH value during the second reaction is lowered and finally maintained at 9.0-11.0; g. After the coprecipitation reaction is completed, the further comprising: performing solid-liquid separation on the system after the coprecipitation reaction is completed, washing, drying, sieving and demagnetizing the solid; h. During the coprecipitation reaction, the mother liquor produced in the coprecipitation reaction is continuously discharged.
8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the positive electrode material includes the positive electrode material precursor having both high capacity and cycle performance as described in any one of claims 1 to 5.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode material according to claim 8.
10. A lithium battery device, characterized in that: Includes the lithium ion battery as claimed in claim 9.